Sleep patterns and quality in Pakistani adults: A Letter to the Editor - Abid, Muhammad Taha; Abbas, Mudassir; Haider, Syed Hamza (Journal of the Pakistan Medical Association, 2023)
None. Applied manuscript is a letter to the editor.